2012
DOI: 10.4014/jmb.1206.06043
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Electrochemical Synthesis of L-DOPA Using Oxidoreductase Enzymes: Optimization of an Electrochemical Process

Abstract: Levodopa or L-3,4-dihydroxyphenylalanine (L-DOPA) is the precursor of the neurotransmitter dopamine. L-DOPA is a famous treatment for Parkinson's disease symptoms. In this study, electroenzymatic synthesis of L-DOPA was performed in a three-electrode cell, comprising a Ag/AgCl reference electrode, a platinum wire auxiliary electrode, and a glassy carbon working electrode. L-DOPA had an oxidation peak at 376 mV and a reduction peak at-550 mV. The optimum conditions of pH, temperature, and amount of free tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Even immobilization of the enzyme is not sufficient to reach considerably higher conversion, although increased stability can be observed in these processing conditions. The final result was that an average substrate conversion of 31–34% was obtained for aerated mixtures containing both enzyme preparations (other authors: 1.9–53%; [ 19 , 20 , 23 , 24 , 29 , 33 ]). Thus, efforts to decrease the effective concentrations of both reactants in the vicinity of the enzyme are necessary.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Even immobilization of the enzyme is not sufficient to reach considerably higher conversion, although increased stability can be observed in these processing conditions. The final result was that an average substrate conversion of 31–34% was obtained for aerated mixtures containing both enzyme preparations (other authors: 1.9–53%; [ 19 , 20 , 23 , 24 , 29 , 33 ]). Thus, efforts to decrease the effective concentrations of both reactants in the vicinity of the enzyme are necessary.…”
Section: Resultsmentioning
confidence: 97%
“…However, the excess AH 2 is unfavorable because ascorbic acid is recognized by tyrosinase as (i) a diphenolic substrate (ascorbate oxidase) [ 31 ] and (ii) a strong inactivator of the enzyme [ 32 ]. These phenomena and low tyrosinase stability are believed responsible for the low reaction yields (1.9–53% L-DOPA) [ 19 , 20 , 23 , 24 , 29 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample treated in this manner was shaken briefly in a vortex mixer. Since formation of L-DOPA complex is time dependent, substantial L-DOPA concentration was determined after one hour spectroscopically at 414 nm [15,16].…”
Section: -2-3 Quantitative Analysismentioning
confidence: 99%
“…This might be the cause for the difference in cathode and anode potential for the electrochemical reaction. Rahman et al [16] conducted the optimization of an electrochemical L-DOPA synthesis and reported that L-DOPA has and oxidation peak at 376 mV and a reduction peak at −550 mV. This peak difference also might be from different working electrode material.…”
Section: -2 Cyclic Voltammogram Of L-dopamentioning
confidence: 99%